Soil bacterial communities in a 10-year fallow rotational shifting cultivation field and an 85-year-old terraced paddy field in Northern Thailand - Noppol Arunrat; Toungporn Uttarotai; Wuttichai Mhuantong; Praeploy Kongsurakan; Sukanya Sereenonchai; Ryusuke Hatano (Environmental Sciences Europe)
Abstract Rotational shifting cultivation (RSC) and terraced paddy farming are the primary rice cultivation systems in the upland areas of Northern Thailand. Despite their prevalence, few studies have compared the microbial communities in these systems, particularly in rhizosphere and bulk soils. This study investigated microbial diversity and abundance in a 10-year fallow RSC field and an 85-year-old terraced paddy field. Results showed that microbial richness and evenness were significantly higher in terraced soils compared to RSC soils. In contrast, RSC soils, lacking contour walls and ridges, are more vulnerable to erosion and leaching, resulting in a loss of essential nutrients like soil carbon and nitrogen. The microbial community in RSC soils is characterized by a greater relative abundance of Firmicutes and Actinobacteria, whereas Proteobacteria and Acidobacteria predominate in terraced soils. Although terraced rhizosphere soils differed significantly from terraced bulk soils, they exhibited lower richness and diversity than the bulk soils. Moreover, no significant differences were observed between RSC bulk and RSC rhizosphere samples. Bacillus was the dominant genus in RSC bulk soil. Geobacter and Sideroxydans were more abundant in the terraced rhizosphere, while Paenibacillus and Effusibacillus dominated the RSC rhizosphere samples. Predicted enzyme abundances indicated that RSC soils were enriched in cellulase, alkaline phosphatase, amidase, and chitinase, reflecting a microbial emphasis on carbon, nitrogen, and phosphorus cycling processes. Meanwhile, terraced soils exhibited higher abundances of nitrite reductase, nitrate reductase, and methane monooxygenase, suggesting enhanced microbial capacities for nitrogen transformation and methane metabolism. Long-term monitoring is recommended to better understand microbial community dynamics and their role in nutrient cycling in these distinct agricultural systems.